Local field potential power of subthalamic nucleus in human brain is not related to scalp EEG topography dynamics in rest. Issue 3 (March 2016) - Damborská, A.; Michel, Ch.; Baláž, M.; Rektor, I.; Vulliémoz, S.
Abstract : Objective: Subthalamic nucleus (STN) is known to have central position in basal ganglia-thalamocortical circuits. Subthalamo-cortical interactions, however, are not precisely known yet. While intracranial EEG directly explores STN, scalp EEG informs about dynamics of cortical activity, which in rest displays discrete periods of electrical stability-functional microstates. To assess subthalamo-cortical relationship, we analyzed STN and scalp EEG signals. Methods: Simultaneous scalp (51–60 electrodes) and intracranial (from STNs) EEG was obtained from four Parkinson disease patients in rest. Topographic analysis was conducted to identify microstate dynamics. Correlations between scalp and STN signals were calculated. Results: Time course of mean scalp power significantly correlated with that of local field potential power of both STNs (STN-LFP power) in delta, theta, alpha, beta, gamma, and 1–40 Hz frequency bands in all subjects ( r -value from 0.07 to 0.72). Microstate analysis identified typical four scalp topographies in all subjects. No correlations were found between time course of spatial correlation coefficients of template topographic maps and that of STN-LFP power in any frequency band ( r -value <0.108). Conclusion: While STN-LFP power was related to scalp EEG power in rest, it was not related to occurrence of scalp topographies. Key message: Although maybe related to cortical activity, STN activity might not be related to occurrence of microstates.